2020
DOI: 10.1371/journal.pone.0230453
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance and usability of the VISITECT CD4 semi-quantitative test for advanced HIV disease screening

Abstract: Background In sub-Saharan Africa, a third of people starting antiretroviral therapy and majority of patients returning to HIV-care after disengagement, present with advanced HIV disease (ADH), and are at high risk of mortality. Simplified and more affordable point-of-care (POC) diagnostics are required to increase access to prompt CD4 cell count screening for ambulatory and asymptomatic patients. The Visitect CD4 Lateral Flow Assay (LFA) is a disposable POC test, providing a visually interpreted result of abov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 12 publications
2
29
0
Order By: Relevance
“…First, integrating our study within an existing community‐based TB‐contact intervention limits its replicability to similar conditions and may overestimate AHD prevalence, due to the high TB burden of the target population (TB index and contacts). Second, the community intervention would have greatly benefited from POC strip tests discriminating above or below 200 CD4 cells/μL on finger‐prick samples [ 80 , 81 ]. This would have allowed for off‐clinic CD4 count testing, enabling a full home‐based POC strategy [ 19 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, integrating our study within an existing community‐based TB‐contact intervention limits its replicability to similar conditions and may overestimate AHD prevalence, due to the high TB burden of the target population (TB index and contacts). Second, the community intervention would have greatly benefited from POC strip tests discriminating above or below 200 CD4 cells/μL on finger‐prick samples [ 80 , 81 ]. This would have allowed for off‐clinic CD4 count testing, enabling a full home‐based POC strategy [ 19 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the long turnaround time for CD4 results experienced in the lower health facilities [ 30 ], where >60% of eligible PWH were reported in our study, could be another reason for the low CD4 testing rates among ART-naïve PWH observed in our study. The use of a semiquantitative cheap point-of-care CD4 test (Visitect CD4 lateral flow assay) has been shown to have high diagnostic accuracy and usability in low-resource settings and has the potential to be decentralized across lower health facilities [ 31 ]. Its impact on the frequency of CD4-directed CrAg screening is currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Clear Blue Digital Pregnancy Test was the first FDA approved digitized test to have been launched in the market in 2003 (Etherington, 2020 ). Lateral flow technology is also in use for rapid HIV testing; Visitect CD4 is an example of a rapid disposable LFA test developed for HIV patients, it quantifies CD4 protein in T-cells (Ndlovu et al, 2020 ). Other examples of POCT technologies include - ProFlow, C.Diff Quik Chek & Sickle SCAN.…”
Section: Commonly Employed Poct Technologiesmentioning
confidence: 99%